Synthesis, Characterization and Metal Adsorption Capacity of Acacia Lignin Based Resin - Aadil, Keshaw Ram; Jha, Rajan; Jha, Harit (Asian Journal of Biological and Life Sciences, 2016)
The present study is focused on the synthesis of ecofriendly adhesives based on Acacia lignin. Alkali lignin extracted from Acacia wood was used for preparation of bio-based resin. Resin was synthesized using lignin as the replacement of petroleum-based phenol through condensation polymerization reaction catalyzed by sodium hydroxide. Structural characterization was performed using Fourier transform infrared spectroscopy (FTIR), Differential scanning calorimetry (DSC), Thermo-gravimetric analysis (TGA) to measure the glass transition temperature and thermal degradation, respectively. FTIR, revealed Acacia lignin resin resemblance in structure with control resin along with higher reactivity. DSC study suggested that the Acacia lignin based resin exhibited higher glass transition (Tg) temperature (Tg = 475.19ºC) as compared to commercial lignosulphonate based resin (Tg = 263.05ºC). The weight loss rate of the synthesized lignin based resin presented slightly different weight loss curves, wherein the main pyrolysis stage was observed at 200-515ºC. The formulated Acacia lignin based resin exhibited uniform morphology and enhanced temperature stability compared with commercial lignosulphonate based resin. Further, the highest metal adsorption capacity was presented by alkali lignin (86%), followed by lignin based resin (79%). The improved properties of the product were attributed to the increased covalent interaction among phenol-formaldehyde and lignin. Thus, lignin based resin can be utilized as adhesive as well as for the formation of composite materials.
Keywords: Acacia lignin; Bio-based resin; DSC; FTIR; Metal adsorption capacity